2012
DOI: 10.1016/j.str.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Ternary Complex of a NaV C-Terminal Domain, a Fibroblast Growth Factor Homologous Factor, and Calmodulin

Abstract: Summary Voltage-gated Na+ (NaV) channels initiate neuronal action potentials. NaV channels are composed of a transmembrane domain responsible for voltage-dependent Na+ conduction and a cytosolic C-terminal domain (CTD) that regulates channel function through interactions with many auxiliary proteins, including fibroblast growth factor homologous factors (FHFs) and calmodulin (CaM). Most ion channel structural studies have focused on mechanisms of permeation and voltage-dependent gating but less is known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
206
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(221 citation statements)
references
References 57 publications
13
206
1
1
Order By: Relevance
“…2 D-F). These data suggest different targeting sites for FGF13 and FGF14 within the AIS, which is remarkable, given the degree of sequence similarity between these two FHFs, particularly within their FGF-like core domains that contain their VGSC binding sites (19,35,36). Together, the distinct localization patterns of FGF13 and FGF14 suggested different roles for these FHFs within hippocampal neurons.…”
Section: Fgf13 and Fgf14 Are Differentially Localized Within Hippocampalmentioning
confidence: 87%
See 1 more Smart Citation
“…2 D-F). These data suggest different targeting sites for FGF13 and FGF14 within the AIS, which is remarkable, given the degree of sequence similarity between these two FHFs, particularly within their FGF-like core domains that contain their VGSC binding sites (19,35,36). Together, the distinct localization patterns of FGF13 and FGF14 suggested different roles for these FHFs within hippocampal neurons.…”
Section: Fgf13 and Fgf14 Are Differentially Localized Within Hippocampalmentioning
confidence: 87%
“…Among the intracellular VGSC regulators are the FGF homologous factors (FHFs), noncanonical members of the FGF superfamily that are neither secreted nor appear to function as growth factors (15)(16)(17)(18). Rather, the four FHFs (FGF11-FGF14) each contain a VGSC interaction site within a homologous FGF-like core domain (19,20) and exert variable effects on VGSC functional properties (21)(22)(23). The importance of FHFs is underscored by loss-of-function or dominant negative mutations in specific FHFs associated with various neurological disorders, which have been attributed, at least in part, to VGSC dysfunction.…”
mentioning
confidence: 99%
“…Известно, что проксимальная половина С-конца содержит шесть спиральных структур (H1-H6), которые имеют решающее значение для установления межцепочечных контактов, а также внутримолекулярных взаимодействий с линкером доменов III и IV, стабилизирующих инактивированное состояние [39]. Мутация E1823HfsX10 усекает С-конец за счет удаления H3-H6, оставляя H1 и H2 неизменными, что может способствовать различиям в вариантах пропускной способности, объясняющим разно-образие клинических проявлений в обследован-ной семье.…”
Section: Discussionunclassified
“…# 2015 International Union of Crystallography conformation the hydrophobic residues in each lobe are buried and held together, which precludes further substrate binding; however, calcium saturation triggers a significant change in the orientation of the helices in two lobes, and this change eventually leads to an 'open' conformation with exposed hydrophobic clefts (Houdusse et al, 2006;Wang et al, 2012). This structural change enables CaM to induce signal transduction pathways that act downstream of the initial detection of the second messenger Ca 2+ (Zielinski, 1998).…”
Section: Issn 2053-230xmentioning
confidence: 99%
“…CaM conveys stimuli signals through alterations in its own structure in response to calcium binding (Snedden & Fromm, 1998;Zielinski, 1998). Previous structural studies on CaM under different conditions have revealed that CaM adopts a 'closed' conformation in the calcium-free state but adopts an 'open' conformation following calcium binding (Feldkamp et al, 2011;Wang et al, 2012). In the 'closed'…”
Section: Introductionmentioning
confidence: 99%